2020
DOI: 10.1101/2020.12.01.20240853
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

International observational survey of the effectiveness of personal protective equipment during endoscopic procedures performed in patients with COVID-19

Abstract: Introduction and aims: This international survey was performed to evaluate the cumulative incidence of nosocomial novel coronavirus disease 2019 (COVID-19) among healthcare professionals during endoscopic procedures. Methods: We performed an international web-based self-reported questionnaire survey. Participants completed the questionnaires every week for 12 weeks. The questionnaire elicited responses regarding the development of COVID-19 and details of the PPE used. Results: All 483 participants were include… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(14 reference statements)
1
1
0
Order By: Relevance
“…However, more than half of the respondents, except those in Singapore, reported that they continued to face some shortages after the first wave. It has been reported that the common PPE used for patients with COVID-19 during endoscopic procedures included surgical masks and N95 masks, face shields, goggles, caps, long-sleeved isolation gowns, and gloves [ 29 ], which are almost consistent regarding the results of PPE for high-risk patients in our study. N95 or equivalent masks were used more frequently for high-risk patients than for low-risk patients.…”
Section: Discussionsupporting
confidence: 87%
“…However, more than half of the respondents, except those in Singapore, reported that they continued to face some shortages after the first wave. It has been reported that the common PPE used for patients with COVID-19 during endoscopic procedures included surgical masks and N95 masks, face shields, goggles, caps, long-sleeved isolation gowns, and gloves [ 29 ], which are almost consistent regarding the results of PPE for high-risk patients in our study. N95 or equivalent masks were used more frequently for high-risk patients than for low-risk patients.…”
Section: Discussionsupporting
confidence: 87%
“…When performing gastrointestinal endoscopy, it is advisable to wear personal protective equipment (PPE), including a mask with a face shield (or a mask and goggles), gloves, a cap, and a gown with long sleeves, and change them for each patient whenever possible [14]. After the examination and treatment are completed, the examiner should then wash themselves from fingers to elbows.…”
Section: Screening For Colorectal Cancer During the Covid-19 Pandemicmentioning
confidence: 99%